PENGARUH SEMANGAT KERJA DAN KECERDASAN EMOSIONAL TERHADAP KINERJA - Yusup, Daman (Coopetition : Jurnal Ilmiah Manajemen, 2018)
This research uses descriptive approach by using questionnaires from 64 respondents, analyzed using quantitative / inferential analysis, where the analysis to test the hypothesis or know the effect of variable X1 and variable Y either simultaneously or partially to variable Y. Ordinal data processing is converted into scale interval using MSI. The results showed that the test results, although small direct influence between variables X1 with variable Y of 28% while the direct influence of variable X2 to variable Y is very big influence is 44.9% and simultaneously variable X1 and variable X2 affect Y variable of 31 , 3%